NEUROLOGICAL MANIFESTATIONS OF COVID-19 IN PATIENTS ADMITTED AT A TERTIARY CARE HOSPITAL IN PUNJAB, PAKISTAN - Saima Shafait (Army Medical College Rawalpindi, 2020)
Objective: To determine the frequency of neurological manifestations and complications of SARS-COV-2. We were especially concerned with the cases where the primary presentation was neurological indicating the neuro-invasive potential of the virus.